Effects of TiO2 and SiO2 additions on phase formation, microstructures and PTCR characteristics of Sb-doped barium strontium titanate ceramics - Bomlai P. (2014)
Phase formation, densification, microstructural development and the electrical resistivity of Sb-doped Ba0.8Sr0.2 TiO3 ceramics, containing different sintering additives have been investigated. A secondary phase of (Ba1-x Srx)6Ti17O40 was found in samples containing 1 mol% excess TiO2, whereas in samples containing a combination of 1 mol% TiO2 and 3 mol% SiO2 an additional fresnoite solid solution phase, Ba1-ySryTi1+xSi2-x O8, was found to co-exist at intergranular regions. Grain growth was suppressed by the single TiO2 additive, but no improvement in densification was observed. However, the combined excess of SiO2 and TiO2 promoted liquid phase sintering, producing a reduction in sintering temperature from ∼1350 °C to ∼1250 °C; this additive combination also enhanced the PTCR response. © 2004 Elsevier Ltd. All rights reserved.